Effective Scheduling of Energy Consumption in Smart Grids - Jaime Paulo Carneiro Azevedo (2013)
Despite the use of cleaner energies, their generation depends on a very specific technology and variable natural factors that make these resources difficult to integrate with the network. This way these energy resources are less usable unless they can take a significant part of base production. In order to be able to take advantage of this, base demand must be constant, meaning that peak demand must be reduced. Thus, the appearance of Smart Grids started a new path in finding solutions for this problem by enabling exchange of information between the producer and the consumer in order to control and advise consumers about their energy usage. Consumption control brings advantages by serving as a top aide in deviation of consumption to non-peak hours. This research will be focused on potentiating Smart Meter capabilities in order to control appliances making energy consumption schedulable.